MOORE–PENROSE INVERSE OF BIDIAGONAL MATRICES. III - Hakopian, Yu.R.; Aleksanyan, S.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
The present paper is a direct continuation of the papers [1, 2]. We obtain intermediate results, which will be used in the next final fourth part of this study, where a definitive solution to the Moore–Penrose inversion problem for singular upper bidiagonal matrices is given.
Keywords: generalized inverse, Moore–Penrose inverse, bidiagonal matrix